Using computers - Dologite, D. G. (New Jersey : Prentice-Hall, 1989)
This book is written to be independent of a particular brand of software. The approach allows an instructor to choose among alternative microcomputer lab software offerings.
Chapter 1. Introduction To Using Computers -- Module 1. Understanding Hardware And Software -- Module 2. Using Personal Productivity Software -- Module 3. Using Database Software -- Module 4. Developing And Using Computer System -- Module 5. Advanced Systems -- Module 6. Special Topics.
Includes bibliographical references and index.
Keywords: COMPUTER PROGRAMMING LANGUAGE